O amadurecimento do bebê e a linguagem: uma leitura a partir de Winnicott e Benveniste - Kruel, Cristina Saling (2015)
This thesis aimed to deepen the concept of mother-infant mutuality experience, demonstrating how it is expressed in semiotic systems, whether verbal or non-verbal, in order to favor the emergence of symbolism and sustain the process of language acquisition by the baby, based on the approximation of the Winnicott theory and semiotic principles found in enunciative theory of Benveniste. A secondary objective was to analyze the relationship between the semiotic principles found from qualitative and quantitative evidences in maternal and child behaviors between one and four months of development, and do the analysis of the transition of an interpersonal development for intersubjective in a baby from four to seven months. Another objective was also to analyze in qualitative and quantitative terms the kind of language addressed to the baby in the first months, especially in differentiating between presence and absence of manhês. Therefore, there were two key developments: the theoretical reading of selected texts of Winnicott and Benveniste, and a longitudinal empirical study of four babies and people who care them, in this study, the biological mothers of babies. It was, therefore, a collective case study that involved four phases of collection, occurring the first 20 to 30 days old babies, the second between 80 and 90 days of babies, the third between 110 and 120 days when infants completed four months of age. Just for one baby was possible to validate and analyze the collection for the fourth stage, when she was next at 7 months of age. The collections were at home, in a day and the most convenient time for the family. In the four steps a film breastfeeding scene was performed, starting at least five minutes before the start of breastfeeding, ending five minutes after. The recordings were transcribed and data analysis, were thought two studies. The first study consisted of qualitative analysis of the transcripts to identify aspects of the baby's maturity, in the light of Winnicott's theory, related, from the idea of a theoretical outer, the enunciation principles linked to the baby's body semiotic system related with maternal language, namely, the principles of interpretância, homology and no redundancy. The second study was conducted through three-minutes analysis of the recordings with the ELAN software for identification of declared categories and maternal and child behaviors based on a social cognition protocol. The analysis showed that the association of mother-infant experience proposed by Winnicott can be observed through benvenisteana idea of semiotic, verbal and nonverbal systems, by the mother and the baby, and in the way they are related. This experience is evident at times when the mother gives sense, interprets and translates the baby signs, filling his place of enunciation, by translation of his/her words in demand, establishing a homology relationship between baby‟s semiotic non verbal system and his verbal semiotic system, through interpretância. In addition, the data shows that, in that the object moves from subjective to objectively perceived, over baby ripening process, communication with it becomes explicit, a fact that indicates the transition from a interpersonal for intersubjective development , which is evident in reducing the use of manhês, and presence of intersubjectivity as a category of social cognition in the second half of life. Finally, it is emphasized that the semiotic principles proposed in this Thesis appear numerically in the behavior of dyads analyzed and, therefore, can be proposed as operative principles in the process of extreme dependence of the maturation process, when the baby still does not speak.